Comparability of compressed sensing-based gradient echo perfusion sequence SPARSE and conventional gradient echo sequence in assessment of myocardial ischemia. Issue 131 (October 2020) - Muehlberg, Fabian; Stoetzner, Arthur; Forman, Christoph; Schmidt, Michaela; Riazy, Leili; Dieringer, Matthias; der Geest, Rob van; Schwenke, Carsten; Schulz-Menger, Jeanette
Highlights: Compressed sensing-based perfusion sequence yields stable image quality and enhanced contrast-to-noise ratio. No differences in visual and quantitative perfusion analysis were observed between both sequences. Compressed sensing-based perfusion sequences enable for increased coverage and/or higher spatial resolution. Abstract: Purpose: Stress perfusion imaging plays a major role in non-invasive detection of coronary artery disease. We compared a compressed sensing-based and a conventional gradient echo perfusion sequence with regard to image quality and diagnostic performance. Method: Patients sent for coronary angiography due to pathologic stress perfusion CMR were recruited. All patients underwent two adenosine stress CMR using conventional TurboFLASH and prototype SPARSE sequence as well as quantitative coronary angiography with fractional flow reserve (FFR) within 6 weeks. Coronary angiography was considered gold standard with FFR < 0.75 or visual stenosis >90 % for identification of myocardial ischemia. Diagnostic performance of perfusion imaging was assessed in basal, mid-ventricular and apical slices by quantification of myocardial perfusion reserve (MPR) analysis utilizing the signal upslope method and a deconvolution technique using the fermi function model. Results: 23 patients with mean age of 69.6 ± 8.9 years were enrolled. 46 % were female. Image quality was similar in conventional TurboFLASH sequence and SPARSE sequence (2.9 ± 0.5 vs 3.1 ± 0.7, p = 0, 06). SPARSE sequence showed higher contrast-to-noise ratio (52.1 ± 27.4 vs 40.5 ± 17.6, p < 0.01) and signal-to-noise ratio (15.6 ± 6.2 vs 13.2 ± 4.2, p < 0.01) than TurboFLASH sequence. Dark-rim artifacts occurred less often with SPARSE (9 % of segments) than with TurboFLASH (23 %). In visual assessment of perfusion defects, SPARSE sequence detected less false-positive perfusion defects (n = 1) than TurboFLASH sequence (n = 3). Quantitative perfusion analysis on segment basis showed equal detection of perfusion defects for TurboFLASH and SPARSE with both upslope MPR analysis (TurboFLASH 0.88 ± 0.18; SPARSE 0.77 ± 0.26; p = 0.06) and fermi function model (TurboFLASH 0.85 ± 0.24; SPARSE 0.76 ± 0.30; p = 0.13). Conclusions: Compressed sensing perfusion imaging using SPARSE sequence allows reliable detection of myocardial ischemia.